Quality improvement through foresight methodology as a direction to increase the effectiveness of an organization - Marcin Olkiewicz (Contemporary Economics, 2018)
The aim of this study was to show that quality improvement through foresight can be an instrument for shaping efficiency in an organization. The author of this article presented his own concept of quality improvement in an organization, which can also be a method for the strategic management and development of various aspects of the organization. The universality of the concept as a tool that is supported by the foresight methodology brings tangible results, as shown through 'quality foresight' at the micro (unit) level. The case examined indicates that each organization should be analyzed individually while retaining the foresight methodology and process. The study also showed that the application of foresight determines the organizational, management and social changes that influence the innovativeness (including the diversification of technological processes and automation), production dynamics (increase by 260%), sales and quality in the organization. The presented research results indicate that 'quality foresight' can potentially become a trend that includes the main strength of quality improvement, the improvement of competitiveness, and the productivity and efficiency in organization development.
Keywords: L21; M11; O31; 330; foresight; quality foresight; improvement; quality; efficiency